Pengaruh Metode Pembelajaran Ceramah terhadap Hasil Belajar pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti di SD Negeri 25 Pasir Tiku - Afrina, Meti; Wirdati, Wirdati (Lembaga Yasin AlSys, 2024)
This research was conducted because there are still students who have low learning outcomes in Islamic religious education subjects. The purpose of this study was to determine whether there is an effect of the lecture learning method on learning outcomes in Islamic education subjects at SD Negeri 25 Pasir Tiku. This type of research is correlation. There are 44 students from class IV and V as the sample of this research. The purposive sampling technique used in the sampling process. Questionnaires and learning outcomes used to collect research data. The results showed that the results of the hypothesis test of the lecture method on learning outcomes were the significance value of 0.000 <0.05 and the t value of 6.078> t table 2.018, so it was concluded that H_0 was rejected, which means that there is an effect of the lecture learning method on the learning outcomes of Islamic religious education at SD Negeri 25 Pasir Tiku.